De novo design of metal‐binding cleft in a Trp‐Trp stapled thermostable β‐hairpin peptide. Issue 6 (18th August 2021) - Lella, Muralikrishna; Mahalakshmi, Radhakrishnan
Abstract: Metals are important molecules in protein biochemistry, as they are involved in various essential biochemical processes. Inspired by the coordination chemistry of metal‐binding proteins, and to improvise the stability of recognition motifs, here we present the design of hyperstable stapled β‐hairpin with a defined metal‐binding cleft. We achieved this by establishing Trp‐Trp covalent cross‐linking in a long‐chain 16‐residue β‐hairpin scaffold, and incorporating a stereospecific Cys2 ‐His2 tetrad as the metal‐binding cleft. This water‐soluble peptide showed broad metal‐binding properties, with Cu 2+ specificity. Importance of the Cys‐His tetrad in metal ion selectivity was established with Asp/Glu substitutions. We propose that such predefined hyperstable β‐hairpins with recognition motifs are useful versatile tools for developing peptide‐based catalysts, and in biomarker design. Abstract :